Visualisasi Ruangan Dalam Piramida Mesir Menggunakan Augmented Reality - Bramatya Mahendra V.N; Suprianto Suprianto; Hindarto Hindarto (Jurnal Algoritma, 2023)
The pyramid is a pyramid-shaped building made of large, sturdy stones. The pyramids are always associated with the country of Egypt, which is indeed the country of origin for the emergence of the pyramid building which is a historical heritage building. Lack of information about the Egyptian pyramids makes it difficult for some people to know the contents and functions of the pyramids. To describe or visualize this building, researchers use Augmented Reality technology as a way to display an overview of the contents of the Egyptian pyramids formed with a 3D model that aims as a medium to make it easier for the public to find information about Egyptian buildings. The method used in this study is the Multimedia Development Life Cycle (MDLC) which consists of Concept, Design, Material Collecting, Assembly, Testing, Distribution. In this study, researchers contributed to creating and developing an Augmented Reality application to introduce interior space in Egyptian buildings made in 3D using the Sketch Up tool. The results of this study are an android-based application that contains visualizations of the Egyptian pyramids and the rooms in the Egyptian pyramids and information about these buildings.